2013
DOI: 10.4321/s1130-01082013001000003
|View full text |Cite
|
Sign up to set email alerts
|

Transcultural adaptation and validation of the Celiac Disease Quality of Life (CD-QOL) survey, a specific questionnaire to measure quality of life in patients with celiac disease

Abstract: Introduction: celiac disease is a chronic condition that requires continued treatment, with the resultant impact on health-related quality of life (HRQOL) of people who suffer it. Most studies in this field have used generic questionnaires to measure HRQOL in celiac patients. It was therefore decided to conduct a study to translate into Spanish and validate a specific questionnaire for celiac disease, the Celiac Disease Quality Of Life Survey (CD-QOL).Objectives: to translate and validate in Spanish the specif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
1
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(42 citation statements)
references
References 26 publications
3
33
1
5
Order By: Relevance
“…28 It is only recently that CD-specific questionnaires have been developed for pediatric 29,30 and adult patients 31,32 and translated into other languages. [33][34][35][36] Although screendetected 37,38 and asymptomatic CD patients 39 seem to have a better QoL than symptom-detected patients at the time of diagnosis, the effect of the GFD is still unclear. Mustalahti et al reported a positive effect of the GFD both in symptomatic and screen-detected patients, 37 Johnston et al suggested the benefits were limited to those presenting with symptomatic disease, 38 Vilppula et al 40 reported no change of the QoL in screen-detected patients on GFD and finally, Ukkola et al described that the QoL improved in symptomatic and in screen-detected symptomatic patients but not in screen-detected asymptomatic patients 41 ( Figure 1).…”
Section: Qolmentioning
confidence: 99%
“…28 It is only recently that CD-specific questionnaires have been developed for pediatric 29,30 and adult patients 31,32 and translated into other languages. [33][34][35][36] Although screendetected 37,38 and asymptomatic CD patients 39 seem to have a better QoL than symptom-detected patients at the time of diagnosis, the effect of the GFD is still unclear. Mustalahti et al reported a positive effect of the GFD both in symptomatic and screen-detected patients, 37 Johnston et al suggested the benefits were limited to those presenting with symptomatic disease, 38 Vilppula et al 40 reported no change of the QoL in screen-detected patients on GFD and finally, Ukkola et al described that the QoL improved in symptomatic and in screen-detected symptomatic patients but not in screen-detected asymptomatic patients 41 ( Figure 1).…”
Section: Qolmentioning
confidence: 99%
“…Previa explicación verbal del estudio a los afectados y familiares en su lengua nativa y llenado del consentimiento informado, se registraron los datos demográficos y se les solicitó el llenado del cuestionario CD-QOL. Según Casellas et al, se considera mala CVRS si el puntaje total es entre 0 y 50 puntos, regular entre 51 y 70 puntos y buena entre 71 a 100 puntos 17 . Las variables fueron procesadas con el programa informático Epi Info © versión 7.2.…”
Section: Materiales Y Métodosunclassified
“…La CVRS puede ser medida por una variedad de cuestionarios tanto generales como específicos para cada enfermedad. El más utilizado es CD-QOL [10][11][12][13][14][15][16][17] . Este instrumento fue aplicado en el sur de Brasil obteniéndose buena calidad de vida en 75% de los encuestados 18 .…”
Section: Introductionunclassified
See 2 more Smart Citations